Wokół "Żyda wiecznego tułacza" - czyli o świętości, zmazie , czasie i przestrzeni = Discussing "The Wandering Jew" - a?few words on sacredness, stigma, time and space - Jarosińska-Buriak, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
By using the anthropological and religious studies tradition as well as the perspective of Judaistconcept of "sacred" time - Sabbath (A.J. Heschel), the article presents the motif of the eternallywandering Jew as described in the novel by Eugene Sue (R. Caillois, R. Otto, E. Levinas). Thediscussed figure is perceived by the author as living a combination of sacredness and stigma, asexperiencing Sacrum that creates distress and uneasiness, and finally as a manifestation of the ideaof the "Other". The most important part of this literary discourse seems to be the demonstrationof the wandering Jew through the Heschel`s idea of Sabbath and the "sanctification" of time, whereJosephs meets God of Sabbath in the convicted Jesus.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); literatura francuska - historia - 19 w.; powieść francuska - 19 w.